Patterns in the production of Apulian red-figure Pottery (Cambridge Scholars Publishing, 2018)
Most of the previous scholarship on Apulian red-figure pottery has focused on the cataloguing of collections, the attribution of vases to painters and workshops, iconographic and stylistic matters, and individual vessels and vase forms. This partly reflects the history of vase-painting scholarship, which grew out of antiquarian collecting during the eighteenth and nineteenth centuries, and the fact that a full archaeological provenance is not preserved for the overwhelming majority of vessels. This book takes a different approach by using a database containing in excess of 13,500 vessels and f.